Deletion of the Small RNA Chaperone Protein Hfq down Regulates Genes Related to Virulence and Confers Protection against Wild-Type Brucella Challenge in Mice - Lei, Shuangshuang; Zhong, Zhijun; Ke, Yuehua; Yang, Mingjuan; Xu, Xiaoyang; Ren, Hang; An, Chang; Yuan, Jiuyun; Yu, Jiuxuan; Xu, Jie; Qiu, Yefeng; Shi, Yanchun; et al. (Frontiers in Microbiology, 2016)
Brucellosis is one of the most common zoonotic epidemics worldwide. Brucella, the etiological pathogen of brucellosis, has unique virulence characteristics, including the ability to survive within the host cell. Hfq is a bacterial chaperone protein that is involved in the survival of the pathogen under stress conditions. Moreover, hfq affects the expression of a large number of target genes. In the present study, we characterized the expression and regulatory patterns of the target genes of Hfq during brucellosis. The results revealed that hfq expression is highly induced in macrophages at the early infection stage and at the late stage of mouse infection. Several genes related to virulence, including omp25, omp31, vjbR, htrA, gntR, and dnaK, were found to be regulated by hfq during infection in BALB/c mice. Gene expression and cytokine secretion analysis revealed that an hfq-deletion mutant induced different cytokine profiles compared with that induced by 16M. Infection with the hfq-deletion mutant induced protective immune responses against 16M challenge. Together, these results suggest that hfq is induced during infection and its deletion results in significant attenuation which affects the host immune response caused by Brucella infection. By regulating genes related to virulence, hfq promotes the virulence of Brucella. The unique characteristics of the hfq-deletion mutant, including its decreased virulence and the ability to induce protective immune response upon infection, suggest that it represents an attractive candidate for the design of a live attenuated vaccine against Brucella.